An Outline of the Concept of Imagination on the Ground of Negativistic Unitarian Metaphysics - Kiedrowski, Krzysztof (Sensus Historiae, 2023)
The theme of this paper is a critical analysis of Leszek Nowak's concept of imagination, proposed in the posthumously published book Subject and the Cultural System (Poznań 2019, ed. I. Nowak). The main theses of the concept are as follows: (1) the activity of imagination consists in applying deformational (counterfactual) procedures (for example: potentialization, reduction, ranscendentalization, ideation, fictionalization), (2) images are not mental constructs, but an objective part of beingness, which is captured in the act of imagination, (3) imagination is limited in terms of grasping negativity. The theses are also the realization of the metaphilosophical programme of radical metaphysics.